IDENTIFIKASI KONTAMINAN TIMBAL DENGAN ELEKTRODA KERJA PASTA KARBON TERMODIFIKASI - Ni Ketut Esati; Kadek Duwi Cahyadi (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
This research identified lead (Pb) contaminants in vegetables. The measurement method used was anodic stripping voltammetry (ASV) with a working electrode of carbon paste modified acid-activated natural zeolite. The stages of the research were formulation of the working electrode, validation of the measurement method and measurement of lead levels in vegetables. The result showed that the optimum formulation of working electrode gave the highest measurement peak current. The optimum formulation with composition of graphite: liquid paraffin: acid activates zeolite is 100:35:10. This electrode was used for determination linear range concentration, limit of detection, percent recovery, and repeatability. The measurement of Pb using electrode by ASV method which gave valid results. It can be seen from a wide concentration range from 50-3000 ppb, a low detection limit of 55.28 ppb, good accuracy and precision. The application of this method is to measure Pb levels in vegetables, and the result is 1.43 mg/Kg.